Photochemical Valence Isomerization to High Energy Products—Bicyclobutanes and Oxabicyclobutanes. (1st July 2021) - Rágyanszki, Anita; Fiser, Béla; Lee‐Ruff, Edward; Liebman, Joel F.
Abstract: DFT calculations were used to determine the structures and energies of bicyclobutane and oxabicyclobutane as valence isomers derived from electronic excitation of their corresponding precursors, 1, 3‐butadiene and acrolein, respectively. Proton affinities of these strained compounds were determined and compared with their simple ring components, cyclopropane and ethylene oxide. The basicity as determined from proton affinities showed that bicyclobutane is the most basic saturated hydrocarbon, even more basic than oxabicyclobutane. Strain energies of these valence tautomers were computed which showed oxabicyclobutane to be significantly more strained than bicyclobutane. Qualitative reasons are provided to account for the difference in strain energies. Abstract : The photochemical valence isomerization of 1, 3‐butadienes give bicyclobutane 1(X=CH2 ) . The stereochemistry of these strained products in substituted derivatives suggest a double disrotatory ring cyclization originating from the second excited state of the diene.. The oxygen analog valence isomerization from acrolein has not been reported nor its product, oxabicyclobutane 1(X = O) . DFT computations for both bicyclics showed a large basicity for the carbon analog exceeding that of the oxygen analog. The strain energy for oxabicyclobutane exceeds that for bicyclobutane. The validity of the computational method is seen from the congruence between experimental and computational values of the structural and thermochemical parameters.